The effects of the crisis in the positioning of Spanish cities - Andrés Precedo Ledo; Alberto Míguez Iglesias (Boletín de la Asociación de Geógrafos Españoles, 2018)
This research is aimed at empirically measuring the impact of the economic crisis (2007-2014) on the changes of positioning and on the resilience of the 22 Spanish cities with a greater demographic and economic weight in the starting line phase. The main objectives are four: to quantify the effects of the economic crisis and the real estate bubble on the changes of positioning in the metropolitan system: to assess the different weight taken by economic initiatives in the private sector, private initiative, and the policies of the public sector: to evaluate the efficacy of strategic and urban marketing policies in the repositioning of cities: and to determine the entrepreneurial profile of urban economy as a factor of resilience and strengthening of urban development.